A Spider‐Capture‐Silk‐Like Fiber with Extremely High‐Volume Directional Water Collection. (2nd June 2020) - Venkatesan, Harun; Chen, Jianming; Liu, Haiyang; Liu, Wei; Hu, Jinlian
Abstract: A spider web collects water by its capture silk for recovering the daytime‐distorted shape during night through water‐sensitive shape memory effect. This unique smart function and geometrical structure of spider‐capture‐silk inspires the development of artificial fibers with periodic knots for directional water collection with vast potential applications in water scarce regions. Existing such fibers are mainly based on nylon filaments coated with petroleum‐originated synthetic polymer solutions. Distinct from using synthetic materials, an all silk‐protein fiber (ASPF) with periodic knots endows extremely high volume‐to‐mass water collection capability. This fiber has a main body consisting of B. mori degummed silk coated with recombinant engineered major ampullate spidroin 2 of spider dragline silk. It is 252 times lighter than synthetic polymer coated nylon fibers that once was reported to have the highest water collection performance. The ASPF collects a maximum water volume of 6.6 µL and has a 100 times higher water collection efficiency compared to existing best water collection artificial fibers in terms of volume‐to‐mass index at the shortest length (0.8 mm) of three‐phase contact line. Since silkworm silks are available abundantly, effective use of recombinant spidroins tandemly shows great potential for scalability. Abstract : All silk‐protein fiber is presented here for its excellent high‐volume directional water collection by using degummed silk and recombinant spidroin engineered major ampullate spidroin 2 as the coating material to fabricate periodic knots. In comparison to previously reported synthetic fibers, remarkable water collection efficiency is observed in terms of volume‐to‐mass index.